“Little Red Jellies” in Monterey Bay, California (Cnidaria: Hydrozoa: Trachymedusae: Rhopalonematidae) - Matsumoto, George I.; Bentlage, Bastian; Sherlock, Rob; Walz, Kristine; Robison, Bruce H. (Frontiers in Marine Science, 2020)
Several species of small, red, deep-sea Trachymedusae have been described and then re-described over the past 20 years, leading to some confusion in the scientific literature. This paper provides an overview of three genera (Benthocodon, Crossota, and Pectis) in the family Rhopalanematidae (Cnidaria: Hydrozoa) that have been observed and examined both in the field and in the laboratory. Twenty years of in situ observations in Monterey Bay indicate that two of the genera, Benthocodon and Pectis, are often associated with the benthic boundary layer and can occur in dense patches. They have been observed resting on soft sediments with their subumbrellar surface down but are also to be found swimming up to several hundred meters above the bottom. Individuals in the genus Crossota tend to be solitary and more pelagic in nature. Although Crossota may be found near the bottom as well, down to depths of 4000 meters, they have not been observed resting on the bottom. The three genera are morphologically similar and difficult to distinguish. As a group, they are small (< 5 cm) and sometimes darkly pigmented, making in situ identifications challenging. We show that these three genera can be differentiated morphologically and we provide a key to the genera and species common in Monterey Bay. Further, the genera differ in their depth distribution and behavior. Molecular genetics suggest that the genera and species are distinct from each other but that their taxonomy is in need of thorough revision. This paper reviews the generic characteristics along with species identifications and provides images and video (supplemental material) that may be helpful in identification.